Determinants of Touristic Attraction in Portuguese Regions and Their Impact on GDP. (June 2015) - Neves, Diana C.; Fernandes, António J.; Pereira, Elisabeth T.
The tourism sector is considered a powerful stimulator of national economies because it affects those economic sectors associated with it, and at the same time creates jobs, increases domestic demand, contributes positively to the balance of payments and allows a better reallocation of wealth. Recognizing this importance, it becomes relevant to investigate the impact of tourism in Portugal at the regional level in order to compare the different Portuguese regions and identify their determinants of attraction. After characterizing the Portuguese tourism market, the authors undertake an empirical analysis, based on a panel data analysis for the Portuguese regions classified by NUTs II and for the period 1990–2007. The results suggest that Lisbon is the region that contributes most to Portuguese GDP because its tourism product is more differentiated.